The Effect of Using Flashcard Media to Improve the Description Writing Skills of Fifth Grade Students at Kendung Elementary School - Dhimas Bayu Pradana; Eni Winarsih; Atri Murtiningsih (Edumaspul: Jurnal Pendidikan, 2023)
This study aims to examine the effect of using flashcard media to improve the skills of writing descriptions in fifth-grade students with a total of fifteen children. The research was conducted at the fifth grade of Kendung Elementary School, located in Kendung Village, Kwadungan District, Ngawi Regency, East Java Province. This research is a class action carried out in the even semester of 2022/2023, and the implementation time is March to April 2023. Classroom action research has three stages: planning, action and observation, and reflecting. Data analysis is quantitative data resulting from implementing learning to write descriptions, student learning outcomes, and field notes. The study results showed that the use of flashcard media improved the description writing skills of fifth-grade students at Kendung Elementary School compared to not use flashcard media. The average value of fifth-grade students increased from the pre-action, first cycle, and second cycle, namely 65.90, 75.50, and 86.26, respectively. The existence of flashcard media in learning to write descriptions shows increased learning. The results of observations show that students are more enthusiastic and enthusiastic in participating in learning